Aborsi akibat Pemerkosaan: Analisis Fikih Perempuan Perspektif Kiai Husein Muhammad dan Santri Lirboyo Kediri - Rahmad Setyawan; Muhammad Asyrofudin; Khairuddin; Muslih; Muhammad Adib Samsudin (LaKaspia, 2025)
The issue of abortion due to rape is one of the complex problems in contemporary women's fiqh, as it involves a conflict between the right to life of the fetus and the protection of victims of sexual violence. Objective: This study aims to conduct a comparative analysis of the views of Kiai Husein Muhammad and Santri Lirboyo Kediri on abortion due to rape and to explore the similarities and differences between the two in the perspective of contemporary women's fiqh. Method: This study is a qualitative study with a comparative approach. The research data was obtained through a literature study by examining the writings and thoughts of Kiai Husein Muhammad and Santri Lirboyo Kediri, as well as other academic sources relevant to the research topic. Results: This study shows that Kiai Husein Muhammad represents a humanistic-progressive fiqh style that emphasizes the preservation of the psychological condition and dignity of women who are victims of sexual violence (hifz al-'Aql), while Santri Lirboyo Kediri is based on traditional-conservative fiqh that emphasizes the protection of fetal life as a form of respect for human rights (hifz an-Nafs). Conclusion: However, the differences between these two views do not necessarily indicate a contradiction, but rather enrich the contemporary fiqh of women on the issue of abortion due to rape by presenting a balance between human values, morality, and submission to the principles of Islamic sharia.